Characterization of a Toxoplasma gondii calcium calmodulin-dependent protein kinase homolog. Issue 1 (December 2016) - Kato, Kentaro; Sugi, Tatsuki; Takemae, Hitoshi; Takano, Ryo; Gong, Haiyan; Ishiwa, Akiko; Horimoto, Taisuke; Akashi, Hiroomi
Abstract Background Toxoplasma gondii is an obligate intracellular parasite of the phylum Apicomplexa and a major pathogen of animals and immunocompromised humans, in whom it causes encephalitis. Understanding the mechanism of tachyzoite invasion is important for the discovery of new drug targets and may serve as a model for the study of other apicomplexan parasites. We previously showed thatPlasmodium falciparum expresses a homolog of human calcium calmodulin-dependent protein kinase (CaMK) that is important for host cell invasion. In this study, to identify novel targets for the treatment ofToxoplasma gondii infection (another apicomplexan parasite), we sought to identify a CaMK-like protein in theT. gondii genome and to characterize its role in the life-cycle of this parasite. Methods An in vitro kinase assay was performed to assess the phosphorylation activities of a novel CaMK-like protein inT. gondii by using purified proteins with various concentrations of calcium, calmodulin antagonists, orT. gondii glideosome proteins. Indirect immunofluorescence microscopy was performed to detect the localization of this protein kinase by using the antibodies against this protein and organellar maker proteins ofT. gondii . Results We identified a novel CaMK homolog inT. gondii, T. gondii CaMK-related kinase (TgCaMKrk), which exhibits calmodulin-independent autophosphorylation and substrate phosphorylation activity. However, calmodulin antagonists had no effect on its kinase activity. InT. gondii -infected cells, TgCaMKrk localized to the apical ends of extracellular and intracellular tachyzoites. TgCaMKrk phosphorylated TgGAP45 for phosphorylation in vitro. Conclusions Our data improve our understanding ofT. gondii motility and infection, the interaction between parasite protein kinases and glideosomes, and drug targets for protozoan diseases.